Gender differences in the evaluation of care for patients with type 2 diabetes: a cross-sectional study (ZODIAC-52) - Steven H. Hendriks; Marco H. Blanker; Yvonne Roelofsen; Kornelis J. J. van Hateren; Klaas H. Groenier; Henk J. G. Bilo; Nanne Kleefstra (BMC, 2018)
Abstract Background Little is known about the association between patient-related factors and patients' evaluation of care. Aim was to investigate which patient-related factors are associated with patients' evaluation of care in men and women with type 2 diabetes (T2D) in primary care. Methods This cross-sectional study included 1102 patients with T2D from 52 general practices. We measured patients' evaluation with the EUROPEP questionnaire and collected demographic, clinical and psychological data from questionnaires and health records. Stepwise linear regression analyses were used. Results The location where the questionnaire was completed (at home or at the general practice) was associated with all outcomes in men and women. Next to this, in men, explanatory factors for the care provider EUROPEP subscale were use of insulin, having some problems with T2D self-care and coffee consumption (R2 8.4%); coffee consumption was associated with the general practice subscale (R2 4.0%). In women, well-being, quality of life, following a general diet, and use of oral glucose-lowering drugs were associated with the care provider subscale (R2 16.8%). For the general practice subscale, well-being and age were explanatory factors (R2 9.4%). Conclusions Only a few factors were found to be associated with patients' evaluation of care for men and women with T2D. Taken together, these factors explained only a small part of the variance of the EUROPEP scores. This explained variance was largely attributable to the location where the questionnaire was completed. We therefore advise to be aware of the possible consequences of filing-out questionnaires about patients' evaluation of care at the general practice. Trial registration NCT01570140 (Clinicaltrials.gov). Registered 29 March 2012.